Evaluasi Pelaksanaan LKMA Bentukan dari Kegiatan PUAP di Provinsi Lampung - valeriana darwis (Journal of Food System & Agribusiness, 2019)
The PUAP program has been implemented since 2008 until 2015 in 52,186 villages and 6,887 LKMA have been formed. Of the 6,887 LKMA that have obtained OJK licenses as many as 115 LKMA and 6 LKMA are in Lampung Province. In implementing the PUAP program, many benefits have been obtained including: helping farmers in business capital loans, increasing income and farmers are used to borrowing money from the banking system. With the many benefits, this paper aims to evaluate the implementation of LKMA that has obtained permission from the FSA. Evaluating the implementation of LKMA uses a ranking method that produces LKMA Mekar Jaya as the best LKMA and this is represented by (i) institutional aspects that already have business legality both from the Ministry of Cooperatives and from OJK, work in the following offices with their devices, hire professional workers with monthly incentives ; (ii) implementation aspects that have given loans to various businesses and differentiate the amount of interest based on the type of business; each borrower is charged a provision fee in each time he borrows and the borrower is the surrounding community who may borrow as long as he follows the requirements and has a loan; (iii) aspects of business development where there was an increase in the number of borrowers and an increase in LKMA's business capital from Rp 150,000,000 to Rp 1,070,000,000